Leveraging Spatial Development Options for Uttar Pradesh - World Bank Group (Washington, DC, 2014)
Uttar Pradesh (UP) is one of the most densely populated states in India with high rates of poverty. The state is a major contributor to the agricultural staples of the country and, at present, a large percentage of the state s labor force is engaged in low-productivity agricultural activities with the agricultural sector employing 60 percent of all formal workers at the state level. The purpose of this report is to present a range of options for regional development in UP by leveraging spatial development patterns along the Eastern Dedicated Freight Corridor (EDFC). The report reflects the Government of India (GoI)-World Bank s India country partnership strategy that promotes balanced regional growth. The report focuses on identifying potential sub regions for logistic hubs and industrial development in the UP districts and develops an economic potential index (EPI) to assess the likely impacts of investments. Using this methodology, four sub-regions have been identified for economic development, namely: (i) Auraiya-Kanpur; (ii) Ghaziabad-Gautam Buddha Nagar; (iii) Aligarh-Hathras-Firozabad-Agra; and (iv) Allahabad-Varanasi. This report is part of a three-phase examination of potential economic development along the EDFC. The report presents the results of economic modeling to determine the best locations in the state to concentrate logistics hubs, industrial estates, and infrastructure investments. The modeling approach assesses six characteristics in each district associated with variations in economic productivity, namely: (i) market accessibility; (ii) industrial diversity; (iii) commodity flow; (iv) per capita industrial investment; (v) agricultural specialization; and (vi) poor social conditions. The report has eight sections, namely: section one is introduction; section two gives overview of UP; section three presents UP s economy and infrastructure: a synopsis; section four gives UP s district economies and economic potential index: key factors; section five presents criteria for locating logistics and industrial hubs within promising sub-regions in UP; section six focuses on moving towards implementation; section seven gives conclusion; and section eight presents annexes.